Russia’s interests in Central Asia in the competition for influence in the region. - Aigarayeva., A. A. (Journal of Oriental Studies, 2016)
Nowadays the Russian Federation is one of the great states that influence Central Asian region. After the collapse of USSR there were some changes in Russian- Central Asian states relations. In the competition for influence with USA and China Russia has own interests in the Central Asia.